CD4+ and CD8+ Counts in Liver and Their Correlation with Necroinflammatory and Fibrosis Grades in Chronic Hepatitis C - Chyntia Olivia Maurine; Rino Alvani Gani; Ening Krisnuhoni; Kuntjoro Harimurti (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2012)
ABSTRACTBackground: Studies on the characteristics CD4+ and CD8+ in hepatitis C and their correlation with the severity of the disease have been rarely conducted. This study was aimed to obtain the mean difference between CD4+ and CD8+ count in liver to evaluate their correlation with fibrosis and necroinflammatory grades in chronic hepatitis C. Method: A cross-sectional study was conducted between March and July 2010 with 30 liver biopsies obtained from patients with non-B and non-HIV chronic hepatitis C who visited the Outpatient Clinic of Hepatology Unit at Cipto Mangunkusumo Hospital in January 2008–February 2010. Fibrosis and necroinflammatory grades were determined using METAVIR methods on liver biopsies. The mean values of CD4+ and CD8+ in portal tracts and hepatic lobules in liver biopsy specimens were evaluated. Statistical analysis was performed by using independent T-test and Spearman test. Results: There was a difference in mean CD4+ counts between portal tracts and the lobules (95% CI = 4.3-17.9; p = 0.002) and also differences in mean CD8+ counts in portal tracts and hepatic lobules (95% CI = 15.4-35.6; p 0.001). There was no correlation between CD4+ and CD8+ counts, either in portal tracts or the lobules, and inflammatory grades as well as the liver fibrosis. Conclusion: CD4+ and CD8+ counts are greater in portal area compared to the hepatic lobules, with greater CD8+ counts than CD4+. However, both CD4+ and CD8+ counts are not correlated to the severity of liver damage.  Keywords: CD4+, CD8+, intrahepatic, chronic hepatitis C, METAVIR